Catalytic activity of high surface area mesoporous Mn-based mixed oxides for the deep oxidation of methane and lean-NOx reduction - Stathopoulos, Vassilis N.; Belessi, Vassiliki; Costa, Costas; Neophytldes, S.; Falaras, P.; Efstathiou, A.M.; Pomonis, Phillippos J. (My University, 2000)
This chapter illustrates the concept of mesoporous materials based on manganese and enriches them with other heterocations, such as A1, La, Ce, at will. The materials thus formed have been tested for important environmentally catalytic reactions: CH4/NO/O2 (lean de-NOx) and CH4/O2 (combustion). Their corresponding catalytic performances were found superior to those reported in the open literature for a large number of catalysts tested under similar experimental conditions. A large number of techniques were employed for the surface and bulk characterization of the present materials. These include X-ray photoelectron spectroscopy (XPS) for surface composition, X-ray diffraction (XRD) for crystal phases, surface area measurements (BET) and AFM/Tapping mode experiments for surface texture, and transient methods for in situ determination of adsorption capacities and interaction characteristics of the reaction molecular species with the catalyst surface. The results obtained from these techniques were correlated with the catalytic performance results obtained.
Keywords: Mesoporous materials; Catalytic reactions; X-ray photoelectron spectroscopy; X-ray diffraction